Cross-cultural adaptation and psychometric validation of the Autism Social Skills Profile in children with autism spectrum disorder in Indonesia - Adela Seftiani; Ika Andrini Farida; Helga Graciani Hidajat (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2025)
Instruments for assessing social skills in children with autism spectrum disorder (ASD) remain scarce in Indonesia, underscoring the critical need for culturally valid tools. This study aims to adapt and validate the Autism Social Skills Profile (ASSP) for use in the Indonesian context through a rigorous cross-cultural methodology. The adaptation process followed the International Test Commission (ITC) guidelines, including forward–backward translation, expert content validation, cognitive debriefing, and psychometric testing. A total of 35 parents of children aged 6–17 years with professionally diagnosed ASD participated in the study. The results demonstrated excellent content validity (Aiken’s V = 0.89–0.92), high internal consistency (Cronbach’s = 0.939), and strong model fit for a refined three-factor structure after removing six items with low discriminatory power (RMSEA = 0.042; CFI = 0.965; TLI = 0.951). The Indonesian version of the ASSP provides theoretical contributions by expanding cross-cultural validation research in ASD assessment and offers practical benefits as a standardized instrument for evaluating social skills and guiding intervention planning in clinical, educational, and community-based settings. These findings support the use of the ASSP as a reliable and culturally relevant tool for improving outcomes in Indonesian children with ASD.